MODEL OPTIMASI LOKASI POS PEMADAM KEBAKARAN (Studi Kasus: Kota Semarang) - Mohamad Bagir; Imam Buchori (TEKNIK, 2012)
Fire is one of the hazards that often occur in urban areas. Many Indonesian cities usually lack of adequatepublic facilities and infrastructures, including facilities of fire hazard. It is important to reduce the risk of firehazard by optimizing the location of fire stations as facility of emergency around the city, so that the impact oflosses can be reduced. For this, defining the location and distribution of fire station should be well considered.This paper aims to discuss the development of an optimization model for fire stations’ location, developed basedon the actual quantity of flammable material, building density, accessibility and the road classes, as a networkanalysis model of Geographic Information System (GIS). In order to observe whether the developed model canwork well, Semarang City is selected as the case study.The application shows that the developed model is satisfy and is able to represent 77.29% of the real conditionof the road network. It is also revealed that the fire stations of Semarang City just presently cover 34.32% of itsarea. Therefore, it is suggested to add six new fire stations, located in Kecamatan Ngadirejo, Tlogo Mulyo,Sambiroto, Pudak Payung, Jatingaleh, and Gunungpati.